“Promoting Creativity and Cultural Awareness in Children through Folk Applied Arts” - Raxmonova Rayxon Zoir qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article explores the significance of folk applied arts in enhancing creativity, aesthetic skills, and cultural awareness in school-age children. Hands-on activities such as designing traditional patterns, working with colors and textures, and crafting ornaments help children develop fine motor skills, visual perception, and problem-solving abilities. Integrating folk arts into educational practice fosters creative thinking, social skills, and appreciation for cultural heritage, providing a holistic approach to child development.